Margins in Sinonasal Squamous Cell Carcinoma: Predictors, Outcomes, and the Endoscopic Approach. (22nd November 2019) - Torabi, Sina J.; Spock, Todd; Cardoso, Bruno; Chao, Janet; Morse, Elliot; Manes, R. Peter; Judson, Benjamin L.
Abstract : Objectives: To identify factors associated with positive margins following surgical management of sinonasal squamous cell carcinoma (SNSCC), especially with regard to endoscopic treatment. Methods: In a retrospective analysis of adult patients with clinically staged tumor (T)1 to T4a SNSCC within the National Cancer Database (NCDB) from 2004 to 2014, factors were associated with positive margins using multivariable binary logistic regression. Cases from 2010 to 2014 had surgical approach (open vs. endoscopic) available and were analyzed in a subgroup to assess the association of surgical approach with margin status. The association of margin status with overall survival (OS) and additional therapy administration was also assessed. Results: We identified 2, 968 cases, of which 807 (27.2%) had positive margins. On multivariable analysis, factors associated with positive margins included higher T stage (T4a vs. T1: odds ratio [OR] 2.768 [95% CI 2.143–3.577]), less differentiated tumors (poorly differentiated vs. well differentiated: OR 1.403 [95% CI 1.060–1.856]), and tumors in the ethmoid sinus (vs. nasal cavity; OR 1.889 [95% CI 1.305–2.734]). Cases treated at higher volume facilities (HVFs) were associated with a lower likelihood of positive margins (OR 0.716 [95% CI 0.582–0.881]). Positive margins were associated with decreased OS (hazard ratio 1.672 [95% CI 1.464–1.908]) and an increased rate of additional therapy (OR 1.966 [95% confidence interval 1.597–2.421]). An endoscopic approach was not associated with an increased likelihood of obtaining positive margins (vs. open; OR 1.151 [0.903–1.651]). Conclusion: Positive margins were less likely when performed at HVFs and more likely in the ethmoid sinus than other subsites. Importantly, there was no association between positive margins and surgical approach. Endoscopic surgery may offer a safe, less invasive alternative to open surgery for select patients. Level of Evidence: NA Laryngoscope, 130:E388–E396, 2020